Unwanted 'hitchhikers' of ornamental snails: a case report of digeneans transported via the international pet trade. Issue 1 (31st December 2022) - Stanicka, A.; Maciaszek, R.; Cichy, A.; Templin, J.; Świderek, W.; Żbikowska, E.; Labecka, A. M.
Abstract: In the European Union, aquarium pets are organisms intended for closed places (e.g., pet shops, garden ponds, home aquariums). Until April 2021, regulations did not require veterinary inspection of these animals within the EU, although there is a potential risk of such organisms being released into the environment along with their symbiotes or parasites. Currently, a "disease-free" declaration is required, but no aquarium snail pathogen that needs attention in international trade has been included in the list of potential hazards. Here, we intended to check whether molluscs from the pet trade could be a source of parasites. We answered this question by using Anentome helena, a popular commodity in the ornamental pet industry, as a research model. Snail specimens were randomly collected from aquarium pet stocks imported from Bangkok (Thailand) to Warsaw (Poland) in March 2020. In total, three specimens were subjected to histological examination and 27 specimens were autopsied. Histological analysis revealed that one snail was infected with rediae (and the cercariae inside them). Our study is the first to show the presence of digenean larvae in A. helena originating from the ornamental pet industry. The spread of such "hitchhikers" in non-native areas will likely be associated with threats to environmental and public health. Therefore, it is necessary to constantly draw public attention to the possible consequences of releasing ornamental pets into the non-native environment.